Anthropometrical and skinfold thickness measurements on the Polar Eskimos, Thule District, North Greenland. - Gilberg, R.; Balslev Jørgensen, J.; Laughlin, William S. (Meddelelser om Grønland, 1975)
Anthropometrical observations on 122 Polar Eskimos from the Thule area, North Greenland are referred and analyzed. Pure Polar Eskimos are compared with hybrids from the Thule District and with corresponding figures from Wainwright Alaska. The Wainwright Eskimos are taller and of heavier body build than the Polar Eskimos. In both places the hybrids are taller than the pure Eskimos. The body proportions are the same in all groups whereas the Wainwright Eskimos have definitely shorter heads than the Polar Eskimos. Skinfold thickness measurements on the Polar Eskimos reveal, that in males the amount of subcutaneus fat, after childhood, remains fairly constant through life. In females, fat is accumulated up to the age of 20, after which time it slowly disappears again through the ages. This investigation was supported by; WHO (G 2/379/1 1963), Statens Videnskabsfond (L 75/68), the Ministry of Greenland, the University of Wisconsin. Laboratory work was carried out in: Universitetets Anthropologiske Laboratorium Nørre Alle 63, Copenhagen Ø.